Temperature dependent black phosphorus transistor and memory. (6th March 2023) - Kumar, Arun; Viscardi, Loredana; Faella, Enver; Giubileo, Filippo; Intonti, Kimberly; Pelella, Aniello; Sleziona, Stephan; Kharsah, Osamah; Schleberger, Marika; Di Bartolomeo, Antonio
Abstract: We studied the temperature dependent transport properties and memory behaviour of ultrathin black phosphorus field-effect transistors. The devices show electrical conductance and field-effect mobility that decreases with the rising temperature. The field effect mobility, which depends also on the gate voltage sweep range, is 283 cm 2 V −1 s −1 at 150 K and reduces to 33 cm 2 V −1 s −1 at 340 K, when the voltage gate sweep range is ± 50 V. The transfer characteristics show a hysteresis width that increases with the temperature and is exploited to enable non-volatile memories with a wider programming window at higher temperatures.